2010
DOI: 10.1051/0004-6361/201015515
|View full text |Cite
|
Sign up to set email alerts
|

67P/Churyumov-Gerasimenko activity evolution during its last perihelion before the Rosetta encounter

Abstract: Context. The comet 67P/Churyumov-Gerasimenko, target of the Rosetta Mission (ESA) was monitored from January to April 2009 during its last perihelion passage before the Rosetta spacecraft encounters the comet nucleus in May 2014. Photometric data were obtained only from January 25 to March 19, 2009 and they were used to monitor the comet gas and dust activity. Non-photometric data are considered for analysing the evolution of the dust coma morphology. Aims. The goal of the campaign was to characterize the come… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
38
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(42 citation statements)
references
References 13 publications
4
38
0
Order By: Relevance
“…There is a peak around perihelion requiring an increase of the active area to ∼ 4% of the surface. Lara et al (2011). The A f ρ value quoted here has been corrected to zero phase (Lara measurements were all taken at ∼ 36 • ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is a peak around perihelion requiring an increase of the active area to ∼ 4% of the surface. Lara et al (2011). The A f ρ value quoted here has been corrected to zero phase (Lara measurements were all taken at ∼ 36 • ).…”
Section: Discussionmentioning
confidence: 99%
“…Schulz et al (2004), Lamy et al (2006) and Lara et al (2005) obtained the first dedicated characterisation observations after it was selected, when the comet was on the outbound leg of its orbit, and still highly active, following its perihelion passage in 2002. As the comet passed through aphelion its inactive nucleus was studied by Tubiana et al (2008Tubiana et al ( , 2011 and Lowry et al (2012), before it was observed in an active state again as it returned to perihelion in 2008 (Tozzi et al 2011;Lara et al 2011). Further authors have studied the longer lived dust trail associated with the comet (Ishiguro 2008;Kelley et al 2008;Agarwal et al 2010), the dust's polarisation (Hadamcik et al 2010), the nucleus thermal properties (Kelley et al 2006;Lamy et al 2008;Kelley et al 2009), and the morphology (Vincent et al 2013) and composition (Schleicher 2006) of its coma over multiple apparitions.…”
Section: Introductionmentioning
confidence: 99%
“…2. An error around 10% on the measures can be estimated from the absolute flux calibration, as already assumed in previous analogous cometary photometric studies (e.g Schulz et al 2003;Tozzi et al 2007;Bertini et al 2009;Lara et al 2011). In our analysis of the Afρ profiles we considered the longest nucleocentric distances to be corresponding to ρ ∼ 50 000 km except in the last observations on September 9.…”
Section: Af ρmentioning
confidence: 93%
“…We discuss below whether our estimation agrees well with that was presented by these authors, and how the dynamical simulations allow the proposed solution to be refined. Lara et al (2011) have shown that the coma of 67P exhibits several dust jets, which indicates that the activity is not isotropically distributed on the surface, but rather enhanced in specific regions of the nucleus. Because these dust jets can potentially be a serious hazard for the spacecraft, especially for the lower orbital phases of the mission, we need to constrain them better.…”
Section: Introductionmentioning
confidence: 99%